(untitled) (One Health Journal of Nepal, 2022)
Introduction: Anxiety and depression are among the most common mental health problems, and they are highly comorbid with each other. Many college students experience several mental health issues because of academic pressure, family expectations, difficult environment, and controlling people. Hence, the objective of the current study was to investigate the prevalence of anxiety and depression in college students of Kathmandu, Nepal, as very limited studies have been conducted in this area. Methods: This was a cross-sectional study conducted in 504 students (317 male & 187 female, age range = 15 to 21 years, mean age = 17.12±0.90 years) of grade 11 and 12 studying in nine randomly selected colleges of Kathmandu valley, Nepal. Participants with chronic medical illness and severe mental disorders were excluded from the study. A semi-structured questionnaire was used to obtain the information related to socio-demography, and the Hospital Anxiety and Depression Scale (HADS) to assess the status of anxiety and depression in college students. Data were entered and analysed using Statistical Package for Social Sciences (SPSS) version 20.0. Results were presented in frequency and percentage. Results: The prevalence of anxiety in college students was 53.97%. Where, 28.57% students had mild anxiety, 18.85% had moderate anxiety, and 6.55% had severe anxiety. Similarly, the prevalence of depression in college students was found to be 39.88%. Where, 22.42% students had mild depression, 13.69% had moderate depression, and 3.77% had severe depression. Conclusion: The prevalence of both anxiety and depression among college students in Kathmandu valley, Nepal, was found to be very high. The Government of Nepal and other concerned bodies should pay attention to this area.